The Empowerment and Product Development of "Terasi Rebon" Processed Seafood Craftsmen as a Leading Potential for Competitive Coastal Areas in Karang Agung, Tuban, East Java - W., Muslichah Erma; Widyaningrum, Mahmudah Enny; Fattah, Abdul; Soehardjoepri (Advances in Social Sciences Research Journal, 2019)
One of the most prominent products from processed seafood from the famous coastal area of ​​Tuban is Terasi. Terasi is a type of food flavouring in the form of pasta, distinctively smelling fermented shrimp, fish or a mixture of both with salt and other additives. In the implementation of the Regional Superior Product Development Program in partnership with UKM Putra Bahari located in Karang Agung village, Tuban, East Java. Where is the production of shrimp paste as a flavouring cuisine? The problem of partners in terms of the company’s production aspects is the production process in which the process of drying raw materials utilizes the availability of sunlight. Where it has an impact on the quality and extent of drying as well as the problem of cleanliness of the process. Then in operational activities have not been done with good operational management, low innovation in production and product variants, so that it needs overall assistance in marketing, financial to tax and production management aspects